Role of Online Customer Ratings in Shaping Purchase Decisions: A Case Study of Erigo Products on Shopee - Handaputra, Muhammad Ivan; Mustikasari, Ati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of Online Customer Rating on consumer purchasing decisions for Erigo products on the Shopee platform. Methodology: This research adopts a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 100 respondents and analyzed using simple linear regression analysis. Results: The results indicate that Online Customer Rating has a negative and statistically significant effect on purchasing decisions, with a regression coefficient of −1.619 and a significance value of 0.000. The coefficient of determination (R²) of 0.787 shows that 78.7% of the variation in purchasing decisions is explained by online customer ratings. Novelty: This study provides empirical evidence of a negative influence of online ratings on purchasing decisions, which contrasts with the commonly assumed positive effect. Findings: The findings support the negative bias theory, indicating that consumers respond more strongly to negative or inconsistent rating information when making purchasing decisions. Originality: The originality of this study lies in its focus on a specific fashion brand within an Indonesian e-commerce platform, highlighting the critical role of rating credibility in digital marketplaces. Conclusions: Managing online customer ratings transparently and consistently is essential to maintain consumer trust and mitigate adverse effects on purchasing decisions. Type of Paper: Empirical Research Paper.